The Effects of Project Triple Constraint on Malaysia Building Projects - Hassan, Ahmed Khalif; Adeleke, A. Q.; Taofeeq, D. M. (International Society for Everant Publisher, 2019)
This study was carried out in order to investigate the effects of project triple constraint (time, cost and quality) on the building projects situated in Kuantan Malaysia. The main goal was to examine a series of barriers that are related to the building projects, most of which were caused by delay in time, cost overrun and poor quality of the projects. Aside from these, the lack of proper planning regarding cost estimation may sometimes lead to overestimation or underestimation, thus resulting in the delay of building projects or incompletion of the task. This study employed quantitative research technique because it is most suitable for the investigation. Data were analysed using both the IBM SPSS version 22 and smart PLS version 3.2.4 software. The general objectives of this research were to examine the size effect between time management, cost management and quality management on building projects. The respondents’ profiles were analysed using the SPSS while smart PLS was used to analyse the research objectives such as independent variable (time, cost, and quality) and dependent variable (building projects). The findings clearly showed that the project triple constraint (time, cost, and quality) had a positive relationship with the construction companies’ building projects.